Simplified MIMO Relay Design for Multicasting from Multiple-Sources - Khandaker, Muhammad; Rong, Yue (IEEE, 2014)
In this paper, we consider a dual-hop multicasting multiple-input multiple-output (MIMO) relay system where multiple transmitters multicast their own messages to a group of receivers with the aid of a relay node, and all nodes are equipped with multiple antennas. We aim at minimizing the maximal MSE of the signal waveform estimation among all receivers subjecting to power constraints at the transmitters and the relay node. We propose a low complexity solution for the problem under some mild approximation. In particular, we show that under (moderately) high signal-to-noise ratio (SNR) assumption, the min-max optimization problem can be solved using the semidefinite programming (SDP) technique. Numerical simulations demonstrate the effectiveness of the proposed algorithm.